The Big Broadcast [videorecording] - Cayado, Tony (Sampaguita Pictures, 1962)
Two star struck teenagers risk the ire of the their strick and abusive aunt when they decide to watch their idols in the Big Broadcast. Sisters Angge (Amalia Fuentes) and Susay (Susan Roces) cannot believe their luck when they are handicapped by the days heartthrobs Eddie Gutierrez and Jose Mari to become their new-screen partners.